2008
DOI: 10.4088/jcp.07m04022
|View full text |Cite
|
Sign up to set email alerts
|

A 6-Month, Double-Blind, Maintenance Trial of Lithium Monotherapy Versus the Combination of Lithium and Divalproex for Rapid-Cycling Bipolar Disorder and Co-Occurring Substance Abuse or Dependence

Abstract: Objective To assess whether combination treatment with lithium and divalproex is more effective than lithium monotherapy in prolonging the time to mood episode recurrence in patients with rapid-cycling bipolar disorder (RCBD) and comorbid substance abuse and/or dependence. Method A 6-month, double-blind, parallel group comparison was carried out in recently manic/hypomanic/mixed patients who had demonstrated a persistent bimodal response to combined treatment with lithium and divalproex. Subjects were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 38 publications
0
68
0
3
Order By: Relevance
“…In a small RCT involving 31 patients with rapidcycling BD and comorbid SUD who were stabilized on the combination of lithium plus divalproex, there was no significant difference in mood relapse rates between patients randomized to continue combination therapy and those who received lithium alone (181). An analysis of 98 patients from the acute open-label phase of this study found that these patients have a poor response to treatment and a high burden of serious medical comorbidity (327).…”
Section: Medicalmentioning
confidence: 77%
See 1 more Smart Citation
“…In a small RCT involving 31 patients with rapidcycling BD and comorbid SUD who were stabilized on the combination of lithium plus divalproex, there was no significant difference in mood relapse rates between patients randomized to continue combination therapy and those who received lithium alone (181). An analysis of 98 patients from the acute open-label phase of this study found that these patients have a poor response to treatment and a high burden of serious medical comorbidity (327).…”
Section: Medicalmentioning
confidence: 77%
“…In a six-month RCT, patients with BD (recent manic episode), SUD, and rapid cycling, who were responders to lithium plus divalproex, were randomized to continue combination therapy or lithium alone (181). Of 149 patients enrolled into the openlabel acute stabilization phase, 31 were assigned to maintenance treatment and 55% relapsed.…”
Section: Rapid Cyclingmentioning
confidence: 99%
“…Lithium and/or divalproex have level 3 evidence 617, 682, 685, 686, 687. Quetiapine failed to provide any benefit in terms of mood and anxiety symptoms in a small subsample of highly comorbid patients with BD.…”
Section: Specific Populationsmentioning
confidence: 99%
“…A combination of divalproex and lithium is the only treatment for alcohol use disorder comorbid with BD that meets criteria for level 2 evidence 682, 683. In a small RCT, there was a significant reduction in the number of drinks per drinking day, as well as per heavy drinking day, in the combination group compared to the group with lithium alone when adherence to treatment was added as a covariate.…”
Section: Specific Populationsmentioning
confidence: 99%
See 1 more Smart Citation